2016
DOI: 10.4238/gmr.15028053
|View full text |Cite
|
Sign up to set email alerts
|

Genotype x environment interaction and its implication in identification of common bean populations with high calcium content

Abstract: ABSTRACT. The common bean is a food with high mineral content. Of the various types of beans cultivated in Brazil, carioca type beans are the most consumed. The aim of this study was to identify promising common bean populations with an emphasis toward the selection of carioca type bean lines with high calcium content. We also aimed to verify whether and how the crop season and the genotype (parental line and hybrid populations) x crop season interaction affect calcium content. A group of 3 lines of good agron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The concentration of Ca in wheat grains varied by 40% between the dry-and humid-seasons-grown wheat grains (Gomez-Coronado et al, 2019). The effect of crop season on the Ca content of common beans showed that the mean Ca content in the dry crop season was 2.6 times higher compared with rainy crop-season-grown counterparts (Fernandes et al, 2016).…”
Section: Environmental Effects On Calcium In Target Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of Ca in wheat grains varied by 40% between the dry-and humid-seasons-grown wheat grains (Gomez-Coronado et al, 2019). The effect of crop season on the Ca content of common beans showed that the mean Ca content in the dry crop season was 2.6 times higher compared with rainy crop-season-grown counterparts (Fernandes et al, 2016).…”
Section: Environmental Effects On Calcium In Target Cropsmentioning
confidence: 99%
“…Breeding studies demonstrated genotypic variability in common bean varieties in the traits responsible for Ca content. Promising common bean populations with high Ca content have been identified, showing that 80% of the Ca content of common beans is concentrated in the seed coat (Fernandes et al, 2016). A hard-to-cook phenotype in the lpa1 common bean line was associated with redistribution of Ca mainly in the cell walls (Cominelli et al, 2020).…”
Section: Genetic Diversity and Transgenic Approachesmentioning
confidence: 99%